EVALUASI KETERSEDIAN RUANG TERBUKA HIJAU (RTH) DI KOTA SOLOK TAHUN 2022 - fendi, Elfi Ef; Syahar, Fitriana (JURNAL BUANA, 2024)
Green Open Space is an elongated/clustered area with open usage, suitable for plant growth. The research aims to analyze the availability and area requirements, as well as the suitability of green open space utilization in the city of Solok in 2022. The method employed in this research is descriptive quantitative. In Ministerial Regulation ATR/KBPN No. 14 of 2022 concerning the Provision and Utilization of Green Open Space, there are three typologies of green open spaces. Typology A, with an area of 820 hectares, consists of urban forests, city parks, district parks, cemeteries, and green corridors. Typology B, Other Functioning RTH Areas, covers an area of 377 hectares, including protected forests, local protection areas, and conservation areas. Typology C, Object Functioning RTH, spans 48 hectares and includes Blue Open Spaces (BOS) such as lakes and rivers. The green open space requirement based on the city's area in Solok is 1,761.6 hectares, while the existing green open space covers 1,245 hectares, approximately 21.2% of Solok city's total area.